2012
DOI: 10.1371/journal.pone.0030720
|View full text |Cite
|
Sign up to set email alerts
|

Common Molecular Etiologies Are Rare in Nonsyndromic Tibetan Chinese Patients with Hearing Impairment

Abstract: Background Thirty thousand infants are born every year with congenital hearing impairment in mainland China. Racial and regional factors are important in clinical diagnosis of genetic deafness. However, molecular etiology of hearing impairment in the Tibetan Chinese population living in the Tibetan Plateau has not been investigated. To provide appropriate genetic testing and counseling to Tibetan families, we investigated molecular etiology of nonsyndromic deafness in this population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Our results also revealed that the SLC26A4 detection rate and incidence of EVA varied geographically. The incidence of inner ear malformation in the Tibetans living in the Tibet plateau was almost as high as that in Chinese Han patients, but the types of malformation in the Tibetan population differed greatly [32]. The most-common inner ear deformity, EVA, is rare in the Chinese Tibetan hearing-loss population.…”
Section: Discussionmentioning
confidence: 96%
“…Our results also revealed that the SLC26A4 detection rate and incidence of EVA varied geographically. The incidence of inner ear malformation in the Tibetans living in the Tibet plateau was almost as high as that in Chinese Han patients, but the types of malformation in the Tibetan population differed greatly [32]. The most-common inner ear deformity, EVA, is rare in the Chinese Tibetan hearing-loss population.…”
Section: Discussionmentioning
confidence: 96%
“…However, this mutation was not found in the 300 healthy individuals. A previous study has shown that c.109G>A was a polymorphism (Yuan et al, 2012), but another study claimed that it is pathogenic. In the study, compound heterozygous mutations in GJB2 were found in four patients.…”
Section: Discussionmentioning
confidence: 99%
“…Four patients showed compound heterozygous mutations carrying c.35delG;c.235delC, c. c.35delG;and c.235delC;respectively. Among the 300 healthy individuals, only two subjects were found to carry heterozygous pathogenic mutation c.235delC with a frequency of 0.67% (2/300); two other variants, c.79G>A and c.341A>G, accounted for 28.67% (86/300) and 14.00% (42/300), respectively. c.79G>A and c.341A>G were polymorphisms that could lead to nonsynonymous changes: p.V27I and p.E114G, respectively (Yuan et al, 2012).…”
Section: Gjb2 Mutationsmentioning
confidence: 99%
“…Previous reports suggest that there is a difference in the prevalence of the 1555A > G mutation among different ethnicities. It was estimated at 8.56% in the northern region with a frequency of 0-3.92% among Uyghurs and 0-1.75% in Tibetans (Li et al, 2010b;Yuan et al, 2012). We speculate that there are several reasons for the racial diversity of hearing levels among the 1555A > G mutation frequencies, such as aminoglycoside antibiotics abuse, some modifying factors increasing the deafness penetrance of mtDNA mutations, and smaller population, but higher endogamy rate in the multiethnic minorities.…”
Section: Figmentioning
confidence: 99%